The level of Psychological Immunity among Secondary School Female Students in the Capital's secretariat-Sana'a - Al-Ammari, Afrah Qasem Yehia; Al-Eryani, Elham Abdullah Mohammed (Journal of Educational and Psychological Sciences, 2023)
This current research aims to identify the level of Psychological Immunity among secondary school female students in Capital's secretariat-Sana'a, in addition, to identify the differences in the level of Psychological Immunity among the female students according to the variables of age and academic level.The researcher used the descriptive approach. The research sample consisted of (500) female students they were selected by stratified Random Sample. The researcher used the list of Psychological Immunity prepared by Olah [2005] after being translated and adapted to fit the Yemeni environment and checking its psychometric efficiency , The results of the research revealed that the level of Psychological Immunity among secondary school female students in Capital's secretariat was above the average, the scores of the list of Psychological Immunity for the sample ranked between (83-165) with an arithmetic mean of (130), Furthermore, the research revealed that there are no statistically significant differences at a level of (α≤0.05) in the level of Psychological Immunity among secondary school female students in Capital's secretariat-Sana'a according to variables of age and academic level , based on the finding of the research , the researcher recommends education offices to prepare and plan psychological counseling programs to enhance the level of psychological immunity among Secondary Students , as well as paying attention to the psychological awareness of the student on how to cope stress through the media, family , school.
Keywords: Psychological Immunity; Secondary school Female Students; Capital's secretariat; Sana'a